2017
DOI: 10.1002/aur.1755
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of neurophenotypes: The consequences of having autism and a big brain

Abstract: A consensus has emerged that despite common core features, autism spectrum disorder (ASD) has multiple etiologies and various genetic and biological characteristics. The fact that there are likely to be subtypes of ASD has complicated attempts to develop effective therapies. The UC Davis MIND Institute Autism Phenome Project is a longitudinal, multidisciplinary analysis of children with autism and age-matched typically developing controls; nearly 400 families are participating in this study. The overarching go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 34 publications
6
87
2
1
Order By: Relevance
“…Our structural MRI findings in this model may contradict the widely known "early brain overgrowth" phenotyping efforts in ASD [35][36][37] , although increases in brain volume in high-risk infants may co-occur with excessive extra-axial cerebrospinal fluid (CSF) 5 . Nonetheless, several studies have suggested divergent age effects on brain morphology changes in ASD 36 , with a more rapid age-related cortical thinning in temporal and parietal regions compared to controls 38 .…”
Section: Asd-like Cerebral and Cerebellar Structural Changescontrasting
confidence: 61%
“…Our structural MRI findings in this model may contradict the widely known "early brain overgrowth" phenotyping efforts in ASD [35][36][37] , although increases in brain volume in high-risk infants may co-occur with excessive extra-axial cerebrospinal fluid (CSF) 5 . Nonetheless, several studies have suggested divergent age effects on brain morphology changes in ASD 36 , with a more rapid age-related cortical thinning in temporal and parietal regions compared to controls 38 .…”
Section: Asd-like Cerebral and Cerebellar Structural Changescontrasting
confidence: 61%
“…Lastly, the current cross‐sectional study in adults with ASD cannot infer causality of the relation between advancing PA and white matter development. Nonetheless, it is invaluable to future studies conducting such investigation in a younger age group …”
Section: Discussionmentioning
confidence: 99%
“…For example, in the 'genetics first' approach, an investigator may be interested in identifying how different highimpact genetic causes for autism may be similar or different at a phenotypic or cognitive level of analysis [88][89][90][91] . In another example, an investigator may compare autism subtypes at the level of neural systems or structural brain features (e.g., with or without early brain enlargement), and then ask the question of whether such a stratification provides a meaningful indicator of differentiation at a clinical level 14 . Both top-down and bottom-up approaches can be useful, depending on the particular research question, and each can highlight different aspects of important heterogeneity in autism.…”
Section: Approaches To Decomposing Heterogeneity In Autism: Top-downmentioning
confidence: 99%
“…This idea relates to what others have discussed regarding autism as an umbrella label referring to many different kinds of 'autisms' 9 and regarding how the scientific community should abandon attempts to continue characterizing all of autism under a single theory 10 . Research has begun along these new directions but is highly fractionated because heterogeneity is discussed across multiple levels of analysis, from genetics 11 , neural systems [12][13][14] , cognition 15 , behavior and development [16][17][18] , and clinical topics (e.g., response to treatment, outcome 19,20 ). Approaches differ in how heterogeneity is decomposed, from utilizing theoretical a priori known stratifiers 21,22 or dimensions, to completely data-driven approaches 12,[23][24][25] .…”
Section: Introductionmentioning
confidence: 99%